Regional odontodysplasia: A rare case series and review - Rajib Sikdar; Avik Narayan Chatterjee; Khooshbu Gayen; Supreet Shirolkar; Anisha Bag; Subir Sarkar (Wolters Kluwer Medknow Publications, 2021)
Odontodysplasia is a rare nonhereditary developmental anomaly of dental hard tissue with unknown etiology, arising from both ectodermal and mesodermal components. Hitchin in 1934 first described it as a localized arrest of tooth development generally affecting one quadrant of the jaw. When it just affects one quadrant, it is referred to as "regional odontodysplasia," but when it crosses the midline and affects more than one quadrant, it is referred to as "generalised odontodysplasia." In this two case series, various types of odontodysplasia have been described, one of which is confined to a single quadrant and the other crossing the midline. The cases of odontodysplasia can only be treated by multidisciplinary approach and restorative and prosthetic rehabilitation and regular follow-up require for improving the quality of life of patients.